Language Fillers Used by Students in Conversation - Gandeza, Christian Cudiamat (Yayasan Sembilan Pemuda Indonesia, 2023)
Language is an essential component of our daily lives and is critical to the advancement of human communication; it is a tool for interjecting into a discussion. This study investigated whether fillers are a basic, useful, but frequently overlooked speaking tactic that will be addressed in this study. How fillers help students improve their communication abilities is not clear. The study used conversational analysis and the participants consisted of eighteen students from the College of Teacher Education, Major in Filipino/English. The responses were coded and categorized. A thematic approach was employed to generate the themes. As a result, language fillers help students improve their speaking abilities. It may boost their confidence, enthusiasm, and fluency in the language by allowing them to share their thoughts, ideas, and experiences, which will improve their overall speaking ability. It allows individuals to improve their language skills by employing various oral speaking strategies to enhance their language skills.